Digital Monitoring: working with the academic abstract in times of pandemic - Ester Denise Tavares Lourenço; Jardeane Reis de Araújo; Pâmela Cínthia Pereira Lopes; Rafael Lisboa da Silva; Adriana Carvalho Capuchinho (Universidade Federal do Oeste da Bahia, 2021)
The production of academic abstracts is approached, considering the voices in writing and the dialogue relations that are built in their production. It aims to describe the experiences of the students monitored in the course Introduction to academic reading and writing, carried out in times of Pandemic, in the production of abstracts in a scientific article. It was considered digital monitoring (Monroe, 1974), reading and midiatic literacies (Lemke, 2010), educational technologies (Kenski, 2003; Capuchinho & Silva, 2020), dialogical relations (Freire, 1987; Amarilla Filho, 2011) and abstract (Carvalho, 2015). In differentiated didactic practices with the participation of students from different courses at the Federal University of Tocantins, the monitoring worked on theory and praxis of reading and writing. This environment of interaction between students, monitors and teacher provided remote and differentiated learning, giving new meaning to teaching-learning practices through educational technology plataforms. Therefore, methods for good reading and writing were rediscovered in a more dynamic reinterpretation.